When does doctor’s recommendation become patient’s resolution? The regulatory potential of procedural justice in the context of compliance with medical advice and the treatment process - Prusiński, Tomasz (Frontiers in Medicine, 2023)
The main aim of the study was to find empirical evidence to answer the following question: If an important personal interest—namely, health and the prospect of a long life—is not enough to motivate a person to follow recommendations from doctors and medical experts, what factor plays a significant role? The author tested the regulatory potential of procedural justice in this context. The sample consisted of 210 participants, patients of independent primary health care facilities and specialist hospital outpatient clinics. The empirical data were analyzed by means of structural equation modeling (SEM). Seven SEM models were tested in the analyses. The adopted analytical strategy brought valuable results. The study supported the main hypothesized relationship, showing that procedural justice was a factor increasing the acceptance of and compliance with medical advice and doctor’s perceived competence. The results of analyses indicate that the fair treatment of patients in health care institutions can be regarded as a significant factor regulating patients’ health behavior. The procedural effect is significant for increasing patients’ positive evaluation of doctors’ competence. Also, the evaluation of a doctor as competent increases patient compliance.